Parental coping socialization is associated with healthy and anxious early‐adolescents' neural and real‐world response to threat. Issue 6 (10th March 2019) - Butterfield, Rosalind D.; Siegle, Greg J.; Lee, Kyung Hwa; Ladouceur, Cecile D.; Forbes, Erika E.; Dahl, Ronald E.; Ryan, Neal D.; Sheeber, Lisa; Silk, Jennifer S.
Abstract: The ways parents socialize their adolescents to cope with anxiety (i.e., coping socialization) may be instrumental in the development of threat processing and coping responses. Coping socialization may be important for anxious adolescents, as they show altered neural threat processing and over reliance on disengaged coping (e.g., avoidance and distraction), which can maintain anxiety. We investigated whether coping socialization was associated with anxious and healthy adolescents' neural response to threat, and whether neural activation was associated with disengaged coping. Healthy and clinically anxious early adolescents ( N  =   120; M  =   11.46 years; 71 girls) and a parent engaged in interactions designed to elicit adolescents' anxiety and parents' response to adolescents' anxiety. Parents' use of reframing and problem solving statements was coded to measure coping socialization. In a subsequent visit, we assessed adolescents' neural response to threat words during a neuroimaging task. Adolescents' disengaged coping was measured using ecological momentary assessment. Greater coping socialization was associated with lower anterior insula and perigenual cingulate activation in healthy adolescents and higher activation in anxious adolescents. Coping socialization was indirectly associated with less disengaged coping for anxious adolescents through neural activation. Findings suggest that associations between coping socialization and early adolescents' neural response to threat differ depending on clinical status and have implications for anxious adolescents' coping. Abstract : Greater positive parental coping socialization was associated with lower anterior insula and perigenual cingulate activation in healthy adolescents, but higher activation in anxious adolescents. Coping socialization was indirectly associated with less disengaged coping for anxious adolescents through neural activation. These results suggest that links between parental socialization behaviors, early adolescents' neural response to threat, and adolescent coping in the real world differ depending on clinical status.